Dançando e jogando em frente à tela: o exergame Just Dance na perspectiva dos jogadores - Paola Luzia Gomes Prudente (2020)
Just Dance is an exergame that is based on imitating the choreography of a virtual dancer on the screen, in which the player participates through body movement interaction. It is believed that the study related to body interaction games should not be limited to questions related to the mechanics and movement of the game, but should be configured with a broader focus, which seeks to understand the relationships between players and the game and the players. diverse interests that permeate this environment. It is precisely in this gap that the intentions of this work are inserted, whose main idea is not to reflect on the game itself, nor on the profile of the players, but on the act of playing as a leisure cultural practice, opening space for new reflections about the dance from the perspective of digital culture. In this sense, some problematizations were built: what appropriations do these players make of the game? What appropriations do these players make of the dance, from the practice of the game? What are the relationships established between these players? Trying to answer these questions, the aim of this study is to describe and analyze the appropriations that Just Dance players make of the game and dance. To achieve the objectives, observation techniques, focus group (FG) and spontaneous conversations were used in a WhatsApp group. The sample consisted of 18 Just Dance players from the state of Minas Gerais, who participated in the qualifiers for the Just Dance World Cup, in the years 2017 and 2018. There were 5 females and 13 males, with the track 17 to 35 years old. The content analysis technique was used to treat the collected information (BARDIN, 1977). The data in the present study provide evidence that the subjects who participated in this research go beyond what was initially planned and proposed for the game, creating from the practice of the game, new forms of appropriation that go beyond the act of playing. This experience allows these players to stop being spectators and users and to actively participate in the creation and circulation of new digital content related to the game and dance.